Tradução, adaptação transcultural e validação de conteúdo da King's Parkinson's Disease Pain Scale (KPPS) para a língua portuguesa do Brasil - Márcia Regina Coimbra Cortez (2021)
Introduction: Pain is one of the most common and troublesome non-motor symptoms of Parkinson’s disease (PD). The King's Parkinson's Disease Scale (KPPS) is the first scale of its kind to evaluate the burden and characterization of various phenotypes of pain in individuals with PD. However, its usage in Brazil requires translation and cultural adaptation. Objectives: The purpose of this study was to adapt the KPPS to Brazilian culture and to assess its content validity using the Delphi method. Materials and Methods: The process of adapting the original instrument to the Brazilian context occurred in two phases: I – translation and cultural adaptation to Portuguese- Brazil and II – content validity evaluation. Phase I followed six stages according to international standards (initial translation, translation synthesis, back translation, review by specialist’s committee, pre-test and submission of documentation to the developers of the original instrument). Following the pilot tests with individuals with PD, the pre-final version of the KPPS-Brazil was developed and submitted to judges to assess content validity using the Delphi method. Results: Pre-final version was tested in 10 subjects with PD in order to check for comprehension of instructions and language. Around 15% of subjects did not fully understand questions, which were reviewed and a new pre final modified version was applied to another 10 individuals with PD. This last modified version was sent to judges in order to assess the content validity of each item and three evaluation rounds were conducted, in which several corrections and changes were accepted. The Content Validity Index (CVI) was calculated to determine the judges’ degree of agreement. At the end, CVI regarding language clarity and practical´s and theorical´s relevance was ≥0,8 for each item and >0,9 for the scale. Discussion: Results demonstrated that the KPPS-Brazil showed a quite satisfactory level of semantic, idiomatic, cultural, and conceptual equivalence. The judges' opinion showed adequate content validity for all of the KPPS-Brazil items and the scale. The use of the KPPS-Brazil will enable an adequate assessment of pain in individuals with PD, contributing to clinical practice and research.